Incorporation and evolution of ZrO2 nano-particles in Pt-modified aluminide coating for high temperature applications - Qian, Lingyi; Xu, Fang; Voisey, K.T.; Nekouie, Vahid; Zhou, Zhaoxia; Silberschmidt, Vadim V.; Hou, Xianghui (Elsevier, 2017)
ZrO2 nano-particles were incorporated into electro-deposited PtAl coatings in an attempt to enhance their performance by exploiting the effect of reactive element oxides. PtAl coatings with and without ZrO2 particles were deposited onto three commercially available Ni-based superalloys: Mar-M247, Mar-M246 and Inconel 718. After aluminising and annealing, thermal cycling oxidation tests were carried out to evaluate the influence of ZrO2 addition and substrate composition. Cross-sectional SEM images were obtained to characterise the coatings after deposition, after heat treatment and after 200 thermal cycles. The addition of ZrO2 particles to PtAl coatings on Mar-M-246 and Inconel 718 appeared to increase the growth of thermally grown oxide and reduce its rumpling. However, such effects were not observed for the addition of ZrO2 particles to the PtAl coatings on Mar-M247. The analysis of the coatings on different substrates revealed and elucidated the interactions between Hf, Al and ZrO2, providing better understanding of reactions of ZrO2 and the influence of the substrate on bond coat behaviour.